1994
DOI: 10.1128/jvi.68.3.1544-1550.1994
|View full text |Cite
|
Sign up to set email alerts
|

Internal translation initiation on poliovirus RNA: further characterization of La function in poliovirus translation in vitro

Abstract: Initiation of poliovirus RNA translation by internal entry of ribosomes is believed to require the participation of transacting factors. The mechanism of action of these factors is poorly defined. The limiting amount of one of these factors, La protein, in rabbit reticulocyte lysates (RRL) has been postulated to partially explain the inefficient translation of poliovirus RNA in this system. To further characterize La activity in translation and to identify other potential limiting factors, we assayed the abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(89 citation statements)
references
References 65 publications
(71 reference statements)
6
79
0
4
Order By: Relevance
“…In the case of poliovirus, several aberrant proteins are synthesized from internal AUGs that are not used in vivo (Dorner et al, 1984). The synthesis of the aberrant proteins is suppressed by the addition of La (Svitkin et al, 1994a) and to some 7152 (5) 0-0 -B extent by hnRNP I/PTB, hnRNP Al and p50 (Y.V.Svitkin, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of poliovirus, several aberrant proteins are synthesized from internal AUGs that are not used in vivo (Dorner et al, 1984). The synthesis of the aberrant proteins is suppressed by the addition of La (Svitkin et al, 1994a) and to some 7152 (5) 0-0 -B extent by hnRNP I/PTB, hnRNP Al and p50 (Y.V.Svitkin, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of RNA binding proteins and translation factors Recombinant La protein was overexpressed in Ecoli and purified as described previously (Svitkin et al, 1994a), except that KCI was substituted for NaCl in the buffers used for the elution of La from the heparin-Sepharose, poly(U)-Sepharose and S-Sepharose columns. This modification significantly improved the yield of La.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various cellular proteins may play a role in this process. For example, the cellular proteins eukaryotic elongation factor 1A (eEFIA), La autoantigen (La), murine proliferationassociated protein-1 (Mppl), poly-r(C)-binding protein (PCBP), and polypyrimidine tract binding protein (PTB) have been shown to bind the 5 UTR of picornaviruses and to enhance translation from picornavirus IRES elements (Blyn et al, 1996(Blyn et al, , 1997Borman et al, 1993;Florez et al, 2005;Hellen et al, 1993;Kolupaeva et al, 1996;Meerovitch et al, 1993;Pilipenko et al, 2000;Svitkin et al, 1994), and some of these cellular proteins have also been observed to bind to the 3 UTR of the Norwalk calicivirus (La, PTB, and PABP) (Gutierrez-Escolano et al, 2003) and the HCV genomic RNA (PTB) ( Fig. 1D) (Ito and Lai, 1999).…”
Section: Enhancement Of Translationmentioning
confidence: 99%